Injury surveillance and training load methods used by health professionals in tennis: an online multinational survey - Méndez, D. H.; Policastro, P. O.; de Oliveira Silva, D. (Journal of Sport Rehabilitation, 2023)
Context: Injury surveillance and training load monitoring are both essential for the development of preventative strategies for gradual-onset musculoskeletal injuries in elite sport. Our aim was to survey health professionals working with elite tennis players on whether and how they monitor injuries and training load. Design: A cross-sectional multinational online open-survey. Methods: The survey was developed and advertised in English, Spanish, and Portuguese languages on social media channels, a tennis academic journal, professional tennis associations, and clinical networks of the research team, from December 2020 to April 2021. Results: 72 health professionals from 27 different countries working with elite tennis players responded to the survey. Injury surveillance is performed by 94% (68/72) of the survey respondents, with only 10% (7/68) using the consensus-recommended Oslo Sports Trauma Research Center questionnaire. Most common barriers identified by health professionals to injury surveillance are time constraints (66%), lack of knowledge (43%), and technology (31%). Training load monitoring is performed by 50% (36/72) of the health professionals working with elite tennis players. Main metrics monitored are weekly differences in training load (72%) and acute:chronic workload ratio (58%). Most common reasons for training load monitoring are injury prevention (94%), training planning (81%), and player feedback (53%). Conclusions: Despite a high percentage of health professionals implementing injury surveillance metrics, most of them do not use any validated method. Only half of health professionals working with elite tennis players monitor training load. Lack of knowledge and technology were the main barriers reported for adequately monitoring injuries.